2001
DOI: 10.1029/2000ja003006
|View full text |Cite
|
Sign up to set email alerts
|

Polar/Toroidal Imaging Mass‐Angle Spectrograph observations of suprathermal ion outflow during solar minimum conditions

Abstract: Abstract. We present observations of the magnitude and variability of escaping suprathermal ions in the energy per charge range of 15 eV/e to 33 keV/e. The data were obtained from the Toroidal Imaging Mass-Angle Spectrograph (TIMAS) on the Polar spacecraft from April 1996 to September 1998 over the Earth's southern Polar cap during solar minimum conditions. The net outflow rates of ionospheric ions derived from this data set are significantly different from those inferred from analysis of similar data obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 30 publications
4
84
2
Order By: Relevance
“…Both are qualitatively consistent with the DE 1 results of Yau et al [1985aYau et al [ , 1985b and with the interpretation by these and other authors [Young et al, 1982]: (1) The O + rate of outflow increases with increasing solar activity, essentially because the associated increase in solar EUV radiation raises the O + scale height in the topside ionosphere, feeding more of these ions into the high-altitude acceleration region, and (2) the summertime hemisphere receives more solar irradiation. The O + seasonal oscillation is less obvious in the Southern Hemisphere statistics of Peterson et al [2001], possibly because of their different computational methods. Rather than applying equation (1) above directly to the differential flux arrays, they have used a more circuitous method of combining previously calculated number densities and mean velocity vectors, which may have enlarged the scatter from rounding errors.…”
Section: Interpretation 621 Altitude Variation Of Ion Outflow Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both are qualitatively consistent with the DE 1 results of Yau et al [1985aYau et al [ , 1985b and with the interpretation by these and other authors [Young et al, 1982]: (1) The O + rate of outflow increases with increasing solar activity, essentially because the associated increase in solar EUV radiation raises the O + scale height in the topside ionosphere, feeding more of these ions into the high-altitude acceleration region, and (2) the summertime hemisphere receives more solar irradiation. The O + seasonal oscillation is less obvious in the Southern Hemisphere statistics of Peterson et al [2001], possibly because of their different computational methods. Rather than applying equation (1) above directly to the differential flux arrays, they have used a more circuitous method of combining previously calculated number densities and mean velocity vectors, which may have enlarged the scatter from rounding errors.…”
Section: Interpretation 621 Altitude Variation Of Ion Outflow Ratesmentioning
confidence: 99%
“…The seasonal variation of these rates and of the O + rates will be interpreted later (section 6.2). For seasonal variation of the Southern Hemisphere outflow of He + ions, see Peterson et al [2001].…”
Section: Seasonal Variationmentioning
confidence: 99%
“…One reason for doing this is to minimize the contribution of other factors (besides substorm activity) that are known to affect ion outflow fluxes. As Peterson et al [2001] and Yau et al [1985] have pointed out, ion outflow fluxes depend on season and solar activity. For our data set, solar minimum conditions apply with the average of the F 10.7 index being 73 (Â10 À22 W m À2 Hz À1 ).…”
Section: Data Descriptionmentioning
confidence: 99%
“…Peterson et al [2001], using data from the Polar/TIMAS instrument, show how outflow rates vary with season. In particular, they see a factor of 2.6 increase in the He + outflow rate from summer to winter.…”
mentioning
confidence: 99%
“…Long-term average ion outflow data by the DE-1, Polar and Akebono satellites (Yau et al, 1985(Yau et al, , 1988Peterson et al, 2001;Cully et al, 2003) revealed a good correlation between the total outflow rate and measurements of the solar and geomagnetic activity, as monitored by the daily F 10.7 and 3h K p indexes, respectively. On the other hand, numerous case studies reported a good agreement between strong disturbances in the solar wind inputs, such as during the passage of an interplanetary shock associated with a coronal mass ejection, and a dramatic enhancement of the ionospheric outflowing ion fluxes (Moore et al, 1999;Strangeway et al, 2000;Fuselier et al, 2002).…”
Section: Introductionmentioning
confidence: 99%